Penerapan media film stop motion dalam pembalajaran IPS pada kelas IV di SD - Hidayat, Muhammad Nur (ARKA INSTITUTE, 2022)
The purpose of this study is to describe the application of the use of stop motion film media in social studies learning in elementary schools. This study used descriptive qualitative method. There are two sources of data from this study, namely class teachers and fourth grade elementary school students. Collecting data from this research using observation, interview and documentation techniques. The data obtained from observation is that the teacher uses stop motion film media in the learning process, with this researchers can find out how the application of stop motion film media in the learning process, especially in social studies learning. In this study, the researchers obtained the results of interviews with classroom teachers and fourth grade students regarding the application of the workings of stop motion film media. The results of observations and interviews of teachers and students showed that the stop motion film media obtained by means of stop motion film media worked well and were very happy with this stop motion film media, with the stop motion film media students' enthusiasm for learning increased and students found it easier to understand learning material being taught.